Optoelectronic device library containing multiple Verilog-A models - Guanliang Chen; Zhigang Song; Xinhe Zheng (Scientific Reports)
Abstract The advancement of the optoelectronic fusion industry has escalated the demands for optoelectronic simulation, yet a comprehensive model library remains unavailable for chip designers. We have utilized the hardware description language Verilog-A to develop an extensive optoelectronic device model library, featuring a full range of device types, unified interfaces, and the capability to simulate the physical effects of devices. Establishing this model library is intended to alleviate the workload of chip designers and reduce development costs.